Point of care HIV testing with oral fluid among returnee migrants in a rural area of Bangladesh. Issue 1 (March 2016) - Alam, Md Shah; Khan, Sharful I.; Reza, Masud; Shahriar, Ahmed; Sarker, Md Safiullah; Rahman, Anisur; Rahman, Mustafizur; Azim, Tasnim
Abstract : Objectives: To determine HIV prevalence and assess the acceptability of HIV testing using oral fluid as a point of care (PoC) test method among returnee migrants in a rural area of Bangladesh. Design: A cross-sectional study. Methods: Matlab is a rural area southeast of Dhaka where icddr, b hosts a health and demographic surveillance system covering 225 826 people of whom 934 are returnee migrants. The sample size of 304 was proportionately distributed among randomly selected households. HIV antibodies in oral fluid were tested using OraQuick Rapid HIV 1/2 antibody test. To understand reasons of acceptability a short questionnaire was applied and 32 in-depth interviews were conducted. Results: Of 304 returnee migrants approached, 97.4% accepted the test. The prevalence of HIV was 0.3% without a confirmatory blood test. Reasons for acceptance included easy accessibility of the test at the door-step which saved resources (i.e., time and money), comfortable test-procedure without any pain and fear, and receiving quick results with confidentiality. Some described knowing HIV status as a way to 'get certified' (of sexual fidelity) and to confront a prevailing silent stigma against migrants. Acceptability was moreover found to be grounded in icddr, b's institutional reputation and its close relationship with the local community. Conclusions: The PoC oral fluid test for HIV has shown for the first time that assessment of HIV prevalence in rural-based returnee migrants is possible. Findings also suggest that PoC oral fluid test has the potential of increasing accessibility to HIV testing as it was found to be highly acceptable.